Bootstrap ARDL on health expenditure, green energy, environmental sustainability, and economic growth nexus in Saudi Arabia - Ageli, Mohammed Moosa (Frontiers in Environmental Science, 2022)
The Bootstrap Autoregressive Distributed Lag (BARDL) cointegration model used to examine whether there is a short and long-run relationship between health expenditure per capita (HEPC), Environmental Sustainability is measured by CO2 emissions per capita (CO2), GDP per capita (GDPPC), and Green Energy is measured by Electric Power Consumption per capita (GEPC) in Saudi Arabia using annual time-series data from 1995 to 2021. The significant results show that there is no long-term cointegration relationship between the variables in Saudi Arabia. Therefore, the Bootstrap ARDL Bound Test offered significant empirical support for the validity of no cointegration between the variables. The empirical data show a unidirectional relationship between GDP per capita and health expenditure, green energy and CO2 emissions per capita. The data also show a bidirectional relationship between health expenditure and CO2 emissions and GDP per growth, furthermore, between green energy and economic growth. These findings would be attractive to policymakers for expanding economic growth and development's environmental and health benefits. Moreover, to reduce the effects of global warming without affecting environmental health or the country's long-term economic prosperity.